2018
DOI: 10.1021/acs.biochem.8b00294
|View full text |Cite
|
Sign up to set email alerts
|

Homodimer Architecture of QTRT2, the Noncatalytic Subunit of the Eukaryotic tRNA-Guanine Transglycosylase

Abstract: The bacterial enzyme tRNA-guanine transglycosylase (TGT) is involved in the biosynthesis of queuosine, a modified nucleoside present in the anticodon wobble position of tRNA, tRNA, tRNA, and tRNA. Although it forms a stable homodimer endowed with two active sites, it is, for steric reasons, able to bind and convert only one tRNA molecule at a time. In contrast, its mammalian counterpart constitutes a heterodimer consisting of a catalytic and a noncatalytic subunit, termed QTRT1 and QTRT2, respectively. Both su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Both h QTRT1 and h QTRTD1 co-localize in mitochondria ( Boland et al, 2009 ). The crystal structure of h QTRTD1 (also called QTRT2) revealed that h QTRTD1 forms a homodimer with striking similarity to that of bacterial TGT ( Behrens et al, 2018 ). Recently, the crystal structure of hTGT in its heterodimeric form and in complex with a 25-mer stem loop RNA has been established ( Sievers et al, 2021 ).…”
Section: Current Knowledge Of the Epigenetic Mechanisms Characterized...mentioning
confidence: 99%
“…Both h QTRT1 and h QTRTD1 co-localize in mitochondria ( Boland et al, 2009 ). The crystal structure of h QTRTD1 (also called QTRT2) revealed that h QTRTD1 forms a homodimer with striking similarity to that of bacterial TGT ( Behrens et al, 2018 ). Recently, the crystal structure of hTGT in its heterodimeric form and in complex with a 25-mer stem loop RNA has been established ( Sievers et al, 2021 ).…”
Section: Current Knowledge Of the Epigenetic Mechanisms Characterized...mentioning
confidence: 99%
“…This quaternary structure has been confirmed to be essential for catalyzing the incorporation of queuine into tRNA [ 31 ]. Recently, the crystal structure of the noncatalytic mouse QTRT2 subunit has been solved and found to confirm the prior suggestion that this subunit is incapable to catalyze the guanine to queuine exchange reaction as catalytic residues, and the residues involved in substrate coordination are largely replaced by chemically different amino acids and thus are extremely unlikely to facilitate queuine binding or even the transfer reaction [ 32 ]. In contrast, alignment of the human QTRT1 sequence with the Z. mobilis TGT reveals this subunit to be likely catalytically active with relevant residues in place.…”
Section: Introductionmentioning
confidence: 77%
“…■ METHODS Gene Expression and Mutagenesis, Protein Production, and Purification. The recombinant, separately performed overexpression of murine QTRT1 and QTRT2 genes as well as the purification of the respective gene products were carried out, as described by Behrens et al 19 The site-directed mutagenesis of the QTRT2 gene was carried out via the QuikChange Lightning kit (Agilent) according to the vendor's instructions. For DNA manipulation, plasmids were prepared using the peqGOLD plasmid miniprep kit (PEQLAB).…”
Section: Acsmentioning
confidence: 99%
“…30,33,35 There is, however, no evidence about the importance of QTRT2 residue Tyr354 for dimer stability since a corresponding aromatic residue does not exist in Z. mobilis TGT. The crystal structure of murine QTRT2, published in 2018, 19 reveals that this residue not only seems to be of relevance for the stability of the TGT heterodimer but also for the stability of the QTRT2 homodimer. Here, it forms a subunit-bridging H bond to the main chain amide of Gln48′.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation